HUBUNGAN KONSUMSI KAROTENOID TERHADAP PEMBENTUKAN KATARAK - M Akmal Hidayat Saadillah K (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Cataract is the opacification of the lens that causes decreased visual acuity and can lead to blindness (Bounce GE, 1979). Cataract becomes more common with increasing age and is a major cause of disability among older adults; > 1 million extractions performed each year in United States (West SK, 1991). Thus, identifying the factors that can delay or prevent the development of cataracts will be important both to improve the welfare of the elderly and to reduce the cost of medical care. Diet (intake) of antioxidants including carotenoids have hypothesized to reduce the risk of age-related cataracts by preventing the oxidations of proteins or lipids in the lens. Will however, epidemiological data regarding this phenomenon limited. Objective: Our objective was to examinecross-sectionallythe associationbetween carotenoidconsumption and cataractin men and women. Methods: This study was a correlative analytic research with cross sectional approach. Samples were 60 people aged â‰¥ 40 years in the village of Brajan, Poor, Bantul already inspected cataract. Analysis of study data using regression test with Chi Square method. Results: The number of respondents with low carotenoids cataract by 45 respondents (97,8%) and the low carotenoids and cataracts are not as many respondents 0 (0%). While the number of respondents with a high carotenoid 0 cataract as many respondents (0%) and the high carotenoid cataract but not as much as one respondent (2,2%). On the results of Chi Square analysis showed that there was a significant relationship between intake of carotenoids against cataract formation because p = 0,022, which means p < 0,05. Conclusion: There was a relationship of consumptions of carotenoids against cataract formation.